Ratings Since the Asian Crisis - Reisen, Helmut (OECD Development Centre Working Papers, 2003)
The increased importance of rating agencies for emerging-market finance has brought their work to the attention of a wider group of observers - and under criticism. This paper evaluates whether the importance of ratings for developing-country finance has changed since the Asian Crisis and whether rating agencies have modified the determinants for their rating decisions. It also provides an analysis on recent suggestions by the Basel Committee on Banking Supervision as these are very important for gauging the future role of sovereign ratings for foreign debt finance in developing countries. While the explanatory power of conventional rating determinants has declined since the Asian crisis, recent rating performance for Argentina and Turkey can still be qualified as lagging the markets, as variables of financial-sector strength and the endogenous effects of capital flows on macroeconomic variables seem to remain underemphasised in rating assessments. The market impact of sovereign ...